Implementasi Literasi Digital pada Kurikulum Pendidikan Agama Islam - M. Mujab Ali Ma'sum; Khuriyah Khuriyah (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This article examines the implementation of digital literacy within the Islamic Religious Education (PAI) curriculum as a response to educational transformation in the digital era. The study aims to analyze strategies for integrating digital literacy into the PAI curriculum, identify the challenges of its implementation, and formulate a contextual model for developing PAI learning based on digital literacy. Using a qualitative research method with a literature review approach and analysis of current curriculum documents, the study found that the implementation of digital literacy in the PAI curriculum remains partial and unsystematic. The findings indicate the need to reformulate the PAI curriculum by comprehensively integrating digital literacy competencies through digital project-based learning, online collaborative learning, and the use of social media for reflective learning. The implications of these findings highlight the urgency of transforming the PAI curriculum to prepare students to become critical, creative, and ethical digital Muslims in the era of technological disruption.